Umístění zevního automatického defibrilátoru a jeho užitečnost - Folke, Fredrik (Clinical Cardiology Alert, 2009)
Public-access defibrillation with automated external defibrillators (AEDs) is being implemented in many countries worldwide with considerable financial implications. The potential benefit and economic consequences of focused or unfocused AED deployment are unknown. METHODS AND RESULTS: All cardiac arrests in public in Copenhagen, Denmark, from 1994 through 2005 were geographically located, as were 104 public AEDs placed by local initiatives. In accordance with European Resuscitation Council and American Heart Association (AHA) guidelines, areas with a high incidence of cardiac arrests were defined as those with 1 cardiac arrest every 2 or 5 years, respectively. There were 1274 cardiac arrests in public locations. According to the European Resuscitation Council or AHA guidelines, AEDs needed to be deployed in 1.2% and 10.6% of the city area, providing coverage for 19.5% (n=249) and 66.8% (n=851) of all cardiac arrests, respectively. The excessive cost of such AED deployments was estimated to be $33 100 or $41 000 per additional quality-adjusted life year, whereas unguided AED placement covering the entire city had an estimated cost of $108 700 per quality-adjusted life year. Areas with major train stations (1.8 arrests every 5 years per area), large public squares, and pedestrianized areas (0.6 arrests every 5 years per area) were main predictors of frequent cardiac arrests. CONCLUSIONS: To achieve wide AED coverage, AEDs need to be more widely distributed than recommended by the European Resuscitation Council guidelines but consistent with the American Heart Association guidelines. Strategic placement of AEDs is pivotal for public-access defibrillation, whereas with unguided initiatives, AEDs are likely to be placed inappropriately.
Keywords: urgentní zdravotnické služby; kardiopulmonální resuscitace; Denmark; elektrická defibrilace; defibrilátory; Male; Cost-Benefit Analysis; Emergency Medical Services; srdeční zástava; Urban Population; Adult; Health Planning Guidelines; analýza nákladů a výnosů; Aged; dospělí; mužské pohlaví; senioři; incidence; Dánsko; dostupnost zdravotnických služeb; Electric Countershock; Heart Arrest; zdravotnické plánování - směrnice; senioři nad 80 let; lidé; Cardiopulmonary Resuscitation; ženské pohlaví; Humans; Aged, 80 and over; Financing, Organized; Defibrillators; Female; financování organizované; lidé středního věku; Incidence; Health Services Accessibility; městské obyvatelstvo; Middle Aged